Uma (re)leitura teleológica da filosofia moral em Kant : por uma necessidade de inclusão do homem na natureza - Alcoforado, Rogério Emiliano Guedes (2009)
Made from the bases of metaphysics, this dissertation is related do Kant‟s moral philosophy. But the itinerary to reach the main speculation used to develop this current understanding of Kant‟s thoughts, it is nothing but an attempt to make the formal rigor more flexible, which has always been associated to Kantian ethics‟ perspectives. From the awareness of what this formalism could be, while a moral arrangement, it is how we will be able to come upon a teleological Kant. That is the fundamental element to comprehend some of the significant aspects in that ethical system, which necessarily comes through the effort to demonstrate the proximity between reason and sensibility, as well as nature and liberty. In this environment, the journey to achieve the autonomy, as the bedrock of liberty and morality, evokes the support of education in Kantian patterns, which enables a course of improvement of the human being, as an individual e, more significantly, as specie. This evolution progress, which tents to reveal the destiny of the humanity, is evolved in the relationship between necessity and finality, as a condition to make the structure of a project to humanity possible. We should mention that it is a rational, an educational and a moral project to be developed in the course of history. As a consequence, the amount of all these elements permits the development of the man‟s natural disposition as a creature that looks for self knowledge , becoming, afterward, dignified to be qualified as a human being. Finally, this study intent to figure out the necessity of the human being inclusion to nature, which happens throughout the acquirement of the individuals‟ conscience